Optimal design and operation of PV-battery systems considering the interdependency of heat pumps. (June 2019) - Liu, Xuezhi; Zhang, Peichao; Pimm, Andrew; Feng, Donghan; Zheng, Menglian
Highlights: Optimal design and operation of PV-battery systems combining heat pumps. Sensitivity analysis was carried out with varied PV capacities and battery prices. The use of heat pumps was found to increase the PV self-consumption generally. The use of heat pumps was found to decrease the storage capacity generally. The impact on the commercial return depends on the PV size and the battery price. Abstract: Critical aspects affecting energy storage revenue include high penetrations of renewable generation such as photovoltaics (PV), and significant changes in patterns of demand as a result of widespread uptake of heat pumps. To assess the impact, an optimisation model using mixed integer linear programming (MILP) is proposed, to simultaneously determine the design and operation of battery energy storage for PV-battery systems featuring heat pumps. The annualised capital expenditure (CAPEX), annual operating expenditure (OPEX), self-consumption ratio (SCR), and internal rate of return (IRR) of PV-battery systems are calculated. Sensitivity analysis is carried out with a range of PV capacities and battery prices to understand the complex impact of heat pumps on PV-battery systems. It is shown that with a 3-tier time-of-use pricing tariff, the widespread use of heat pumps generally increases the SCR through the consumption of midday surplus PV, and decreases the optimal capacity of the battery storage. The sensitivity and scenario analysis provides evidence which negates the hypothesis that increased heat pump penetration leads to increased commercial return for PV-battery systems.